KOMITMEN PARTAI POLITIK TERHADAP PENCALONANPEREMPUAN SEBAGAI ANGGOTA LEGISLATIF DALAM UPAYA REALISASI UNDANG-UNDANG NO. 12 TH. 2003 DI PEKANBARU - Sofia Hardani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
The involvement of women in formal politics in Indonesia began to be taken into account since the enactment of the Electoral Law No. 12 In 2003, on the General Election. In Act specified 30% representation of women from all political parties in the parliamentary candidates in national and local level. In Riau Province, the representation of women in parliament has increased. but have not been able to meet the 30% quota for women. This is due to the attitude of the political parties have tended masculine. Undertake research to uncover the commitment of political parties to the nomination of women as members of the legislature in an attempt realization of law no. 12 of 2003 in the province of Riau. This study is a qualitative study, obtained by interview and observation to the board of DPD Golkar, PAN, PKS and the female candidates of political parties elected to the Legislative Council Pekanbaru period 2009-2014. The findings show the phenomenon of “halfhearted” of the party leadership to implement article 65, paragraph 1 of Law No. 12 in 2003 and are not genderresponsive policies, most party leaders still view women as “second class citizens” who do not deserve to sit in the first sequence number representing the party